Enhancing the Backbone Coplanarity of n-Type Copolymers for Higher Electron Mobility and Stability in Organic Electrochemical Transistors - Maria, Iuliana P (Chemistry of materials : a publication of the American Chemical Society, 2022)
© 2022 The Authors. Published by American Chemical Society.